Anodizing of AA6063 aluminium alloy profiles: Generation of dark appearance. (15th January 2013) - Ma, Y.; Zhou, X.; Thompson, G. E.; Nilsson, J‐O.; Gustavsson, M.; Crispin, A.
<x xml:space="preserve">Abstract</x> The generation of dark appearance on an anodized AA6063‐T6 aluminium alloy profile has been investigated. Plan and cross‐sectional views of the anodic films of normal and dark samples revealed a distinct layer, of 1–2 µm thickness, decorated with characteristic features in the outer film regions of the dark sample, contrasting with typical porous anodic film of the normal sample. Additionally, it was revealed that the alloy substrate of the dark sample was over‐aged and the characteristic features in the outer film regions of the dark sample are related to preferential anodizing of coarsened β′ (Mg2Si) precipitates. Further, it is suggested that the over‐aged microstructure is not the sufficient condition for the occurrence of dark appearance, and the anodizing conditions in the early stages also play an important role in the generation of dark appearance. Copyright © 2013 John Wiley & Sons, Ltd.